The Emirs Of Sultan Husayn Mirza (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the transformation of the political elite during the era of Sultan Husayn Mirza – the corps of emirs – from a traditional military class into a complex socio-political institution. Using Zahiriddin Muhammad Babur’s “Baburnama” as the primary source, the article explores the changing concept of "beklik" (lordship) through his descriptions of the emirs. It reveals the growing importance of cultural capital (knowledge, poetry, patronage of the arts) alongside military might in the legitimization of power. The analysis demonstrates that through Babur’s pragmatic gaze, we can observe not only the sophisticated cultural environment of the Herat court but also the evolution of patronage into a political force. This process had a dual impact on the stability of the Timurid empire: on one hand, it fostered an unprecedented cultural renaissance, while on the other, it laid the groundwork for political fragmentation